Current sociolinguistic issues in America - Hadžija Sunaj (Univerzitetska Misao)
The paper examines current sociolinguistic issues in America. Current sociolinguistic issues in America include a variant of English language spoken in the United States, and include domestic variant of native speakers, as well as ethnic variats such as African American English and Native American English and American slang. Historically, the roots of Native American English are found in seventeenth - century at the first immigrants from the East Coast. The first to exert a formative influence on American English were the Scots of Ulster and their influence, which had a direct continuation in Appalchian English. Later, a large number of other European nationalities who emigrated to America throughout their history, such as Germans, Scandinavians, Duthc, French, Poles and Italians, also contributed to the development of the English language in America.